Stent patency in patients with distal malignant biliary obstruction receiving chemo(radio)therapy - Haal, Sylke; van Hooft, Jeanin E.; Rauws, Erik A. J.; Fockens, Paul; Voermans, Rogier P. (Endoscopy International Open, 2017)
Background and study aims Recent literature suggests that chemo(radio)therapy might reduce the patency of plastic stents in patients with malignant biliary obstruction. Whether this might also be valid for other types of stents is unknown. The aim of this study was to determine the influence of chemo(radio)therapy on the patency of fully-covered self-expandable metal stents (FCSEMSs) and plastic stents.Patients and methods We retrospectively reviewed the electronic medical records of patients with distal malignant biliary obstruction who underwent biliary stent placement between April 2001 and July 2015. Primary outcome was duration of stent patency. Secondary outcome was stent patency at 3 and 6 months. We used Kaplan–Meier survival analyses to compare stent patency rates between patients who received chemo(radio)therapy and patients who did not.Results A total of 291 biliary stents (151 metal and 140 plastic) were identified. The median cumulative stent patency of FCSEMSs did not differ between patients receiving chemo(radio)therapy (n = 51) and those (n = 100) who did not (P = 0.70, log-rank test). The estimated cumulative stent patency of plastic stents was also comparable in 99 patients without and 41 patients with chemo(radio)therapy (P = 0.73, log-rank test). At 3 and 6 months, FCSEMS patency rates were 87 % and 83 % in patients without chemo(radio)therapy and 96 % and 83 % in patients with therapy, respectively. Plastic patency rates were 69 % and 55 % in patients without and 85 % and 39 % in patients with therapy, respectively. After 1 year, 78 % of the FCSEMSs were still patent in patients without chemo(radio)therapy and 69 % of the FCSEMSs were still patent in patients with therapy.Conclusion Our data indicate that chemo(radio)therapy does not reduce the patency of biliary fully-covered metal and plastic stents.